PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK - Kautsar, Muhammad; Triansyah, Andika; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe formulation of the problem in this study is whether there is an increase in student learning outcomes against squat style long jumps, the purpose of this study is to describe the improvement in student learning outcomes in physical education learning. The research used was Classroom Action Research, the subjects of 25 students consisting of 15 women and 10 men were carried out during learning as much as 2 cycles. (1) From the results of inter-cycle comparisons concluded that through the learning process the application of the discovery learning model in class X Bawari Islamic High School Pontianak experienced an increase in each action, (2) In each cycle, the completeness value increased in the pre cycle there were 9 complete or 36% of the total number of students, in cycle 1 there were 18 students who completed or 72% of the number of students and in cycle 2 there were 23 complete students or 92% of the total number of students, (3) learning discovery learning models of participants students build a model of knowledge, find steps in finding solutions to material that must be mastered by students, (4) With the application of discovery learning model learning, learning is more fun.Â Keywords: Discovery Learning Model, Learning Outcomes, Long Jump